2022
DOI: 10.17582/journal.pjz/20211201051249
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LncRNA CASC7/ miR-26/ASPN/TGF-β/Smad Axis in Endometrial Cancer

Abstract: Authors' Contribution MI and MR collected the samples. MI compliled the data. JK supervised the research and wrote the manuscript. ZR peformed statistical analysis. MI, MR and KK presented methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Zhang et al found that ASPN expression was higher in normal endometrial tissue compared to EC tissue. Additionally, the authors speculate that lncRNA CASC7 inhibits miR-26, inhibits ASPN, inhibits TGF-β, and promotes XIAP, to activate the SMAD/XIAP pathway in EC, thus improving survival and the invasiveness of endometrial cancer cells [ 33 ] PRELP protein may function as a molecule anchoring basement membranes to the underlying connective tissue [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that ASPN expression was higher in normal endometrial tissue compared to EC tissue. Additionally, the authors speculate that lncRNA CASC7 inhibits miR-26, inhibits ASPN, inhibits TGF-β, and promotes XIAP, to activate the SMAD/XIAP pathway in EC, thus improving survival and the invasiveness of endometrial cancer cells [ 33 ] PRELP protein may function as a molecule anchoring basement membranes to the underlying connective tissue [ 34 ].…”
Section: Discussionmentioning
confidence: 99%